The Correlation between Abdominal Circumference and Psoriasis Vulgaris Incidence - Vrenda Alia; Muhammad Eko Irawanto; Laura Noviani; Ivani Ivani; Nurul Hidayati (International Journal Labs, 2025)
Psoriasis is a chronic inflammatory skin condition that is often associated with various comorbidities, including cardiovascular disease, obesity, diabetes mellitus, and psoriatic arthritis. Obesity, particularly abdominal obesity, is known to impact the effectiveness of psoriasis treatment. This study aims to explore the relationship between abdominal circumference and the incidence of psoriasis in patients at the Dermatology and Venereology Polyclinic of Dr. Moewardi Hospital, Surakarta. The objective of this research was to determine whether abdominal circumference (waist circumference) is associated with the incidence of psoriasis in patients at the Dermatology and Venereology Polyclinic. A cross-sectional study was conducted with 30 psoriasis vulgaris patients treated at the clinic from July to August 2024. Waist circumference was categorized as high or normal. Data analysis was performed using the Mann-Whitney test and logistic regression analysis. The majority of participants (70%) had high waist circumference. Statistically, only age showed a significant relationship with psoriasis incidence (p = 0.015). Gender, BMI status, and waist circumference did not significantly correlate with psoriasis incidence (p = 0.069, p = 0.789, p = 0.284, respectively). This study suggests that waist circumference does not have a significant relationship with the incidence of psoriasis. Future research could explore other factors contributing to psoriasis exacerbation, such as metabolic syndrome or visceral adiposity.